A Transitivity Analysis of Miranda in Sexy: the Character in Jhumpa Lahiris Short Story - Tia Xenia (Journal of Language and Literature, 2014)
Recently, discourse analysis is very popular in analyzing literary text. One of approaches to analyze texts is using transitivity in Systemic Functional Grammar developed by Halliday. Therefore, in this paper, transitivity is employed to analyze the character, Miranda, in Jhumpa Lahiri short story. Because of the different processes, sentences or lines related to the character, Miranda, were collected and later were analyzed. The result shows that the mental process, the verbal process, the behavioral process, the material process, the relational process, and the existential process appear in the short story. It indicates that the writer wants to characterize deeply about the main character who took an important role in the story. Moreover, the mental process is dominant to appear in the story. By this frequent occurrence, we can see that the writer wants to convey the message that Miranda is a thinker who eventually realizes that having an affair is not fair to both the mistress and the wife.Keywords: short story, systemic functional grammar, transitivity approach